PENGARUH PUPUK NPK MUTIARA DAN PUPUK KANDANG SAPI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN CABAI MERAH KERITING VARIETAS ARIMBI (Capsicum annuum L.) - Maria Eka Prasetya (Universitas 17 Agustus 1945 Samarinda, 2014)
The Effect of NPK Mutiara Fertilizer And Cow Manure on the Growth and Yield of Curly Red Chili (Capsicum annuum L.), Arimbi Variety. Objectives of the research were to know the effect of NPK Mutiara fertilizer and cow manure as well as its interactio on the growth and yield of curly red chili varieties Arimbi.The research to start was from February 2013 to June 2013, carried out at Asa Gemuhan Village, Barong Tongkok Sub District of West Kutai Regency, East Kalimantan Province.The research design employed was Completely Randomized Design (CRD) with factorial 3x3 and five replications. The first factor was application of NPK Mutiara Fertilizer (M), that consisted of three sub-factors : NPK Mutiara fertilizer 150 kg per ha or equal 1.5 g per polybag (m1), 300 kg per ha or equal 3 g per polybag) (m2) and 450 kg per ha or equal 3 g per polybag (m3). And second factor was Cow Manure (K), consisted of three sub-faktor : no cow manure (k0), 5 ton per ha or equal 50 g per polybag (k1) and 10 ton per ha or equal 100 g per polybag (k2).Results of the research revealed that the application of NPK Mutiara fertilizer (M) significantly on plant height 40 days and 60 days after planting and age of plant harvested, but did not affect significantly on age of plant height 20 days after planting, the number of branches, the age of flowering, number of fruits per crop and fruit weight per crop.The cow manure (K) did not a affected significantly on plant height at 20 days, 40 days and 60 days after planting, the number of branches, age of flowering ,age at harvested, number of fruits per crop and fruit weight per cropThe interaction between cow manure and NPK Mutiara fertilizer did not affected significantly on plant height at 20 days, 40 days and 60 days after planting, the number of branches, age of flowering, age of harvested, number of fruits per crop and fruit weight per crop.